2015
DOI: 10.1007/s13224-015-0742-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and Doppler Study to Predict Uterine Receptivity in Infertile Patients Undergoing Embryo Transfer

Abstract: About the Author AbstractPurpose To detect whether ultrasonographic parameters and Doppler analysis of uterine blood flow can be of value in the prediction of endometrial receptivity in infertile female patients undergoing embryo transfer. Methods In this study, a total of 200 women with primary infertility undergoing embryo transfer were analyzed. Transvaginal ultrasonography was done on the 10th day of the menstrual cycle. To assess the uterine receptivity, we analyzed all the ultrasonographic and Doppler pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 16 publications
(20 reference statements)
1
24
1
Order By: Relevance
“…5 Although we noticed that levels of the sub-endometrial blood RI in the pregnant group were significantly lower as compared to the non-pregnant group in both study groups, but it was much less in the letrozole as compared to the CC group. 10 In addition, the correlation between VEGF and RI in the letrozole group was significantly negative, improving the endometrial receptivity in the letrozole group, which can be attributed to the increased endometrial VEGF levels with subsequent improved vascularization. 20,22 Clomiphene citrate can downregulate the VEGF production, which may in part be due to its anti-oestrogenic effects.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…5 Although we noticed that levels of the sub-endometrial blood RI in the pregnant group were significantly lower as compared to the non-pregnant group in both study groups, but it was much less in the letrozole as compared to the CC group. 10 In addition, the correlation between VEGF and RI in the letrozole group was significantly negative, improving the endometrial receptivity in the letrozole group, which can be attributed to the increased endometrial VEGF levels with subsequent improved vascularization. 20,22 Clomiphene citrate can downregulate the VEGF production, which may in part be due to its anti-oestrogenic effects.…”
Section: Discussionmentioning
confidence: 93%
“…This can be partially explained due to the fact that these vascular changes play a significant role in the implantation process as they are present from the beginning of the embryo nidation stage . Previous studies showed that good blood supply to the sub‐endometrial halo and to the endometrium results in a thicker endometrial wall maximizing the chance of pregnancy …”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Most suitable endometrial thickness was 10-14mm, followed by 7-9mm. 5 Endometrium <6 mm is associated with no conception. We found decreased pregnancy rate in patients with endometrial thickness more than 14mm.…”
Section: Endometrial Zonesmentioning
confidence: 99%
“…Distinct five line or triple layer pattern of endometrium shows better implantation rate as compared to hazy, homogenous endometrium shown in Table 3. 4,5 Endometrial thickness and subendometrial blood flow patterns are useful prognostic parameters for successful pregnancy. Endometrial blood flow was directly correlated with pregnancy outcome following embryo transfer.…”
Section: Endometrial Zonesmentioning
confidence: 99%